THE EFFECT OF CALF STARTER RATION FOR PRE-WEANING ONGOLE GRADE (PO) CALVES ON BODY WEIGHT GAIN - Winarti, E.; Widyastuti, A. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
The objective of study was to determine the effect of calf starter in the pre-weaning calves against the daily body weight gain. Twenty Ongole grade (PO) calves age of 1 month divided into 4 treatment groups of feed, 5 calves for each treatment. Treatment (P1) fed with extra soybean groats; (P2) soybean groats 50% + Gliricidia 50%; (P3) soybean groats 50%+ rice bran 50%; (P4) soybean groats 50%+ rejected bread 50%. Calf starter was given at age 1 month to 3 months. Observation was carried out on calves daily weight gain. This experiment was designed in Completely Randomized Design. Data was  analyzed by analysis of variance and continued Least Significant Difference Test. Statistical analysis showed that feed of (P <0.05) significantly affected the daily weight gain of the calves. Results of the study can be concluded that calf starter with soya groats provide the best daily weight gain of pre-weaning calf.